Dependence of Temperatures and Kinetic Freeze-Out Volume on Centrality in Au-Au and Pb-Pb Collisions at High Energy - Muhammad Waqas; Fu-Hu Liu; Zafar Wazir (Advances in High Energy Physics)
Centrality-dependent double-differential transverse momentum spectra of negatively charged particles (π−, K−, and p¯) at the mid(pseudo)rapidity interval in nuclear collisions are analyzed by the standard distribution in terms of multicomponent. The experimental data measured in gold-gold (Au-Au) collisions by the PHENIX Collaboration at the Relativistic Heavy Ion Collider (RHIC) and in lead-lead (Pb-Pb) collisions by the ALICE Collaboration at the Large Hadron Collider (LHC) are studied. The effective temperature, initial temperature, kinetic freeze-out temperature, transverse flow velocity, and kinetic freeze-out volume are extracted from the fitting to transverse momentum spectra. We observed that the mentioned five quantities increase with the increase of event centrality due to the fact that the average transverse momentum increases with the increase of event centrality. This renders that larger momentum (energy) transfer and further multiple scattering had happened in central centrality.